RETRACTED: Research on Rural Revitalization and Governance From the Perspective of Sustainable Development - Lu Xu; Hongyang Zhao; Veronika Chernova; Veronika Chernova; Wadim Strielkowski; Guannan Chen; Guannan Chen (Frontiers in Environmental Science, 2022)
The Chinese government has long attached great importance to rural revitalization. The harmony and stability in rural areas are the fundamental guarantees of rural sustainable economic growth and farmers’ prosperity, and they rely on effective rural governance. Taking the Fu’an City in Fujian Province of China as an example, this paper analyzes the rural governance problems arising from the implementation of the rural revitalization strategy with the method of dynamic games with incomplete information after data collection by on-the-spot investigation and file inquiry, etc. The results show that the “solicitation” behavior of village B to increase its own income does not maximize the income of village B and village N; Even under the optimal state of income distribution is derived through the game model, the income distribution between the two villages is still unfair to village N, the investor of the “Waterlands Resort”. Therefore, in order to solve the rural governance problems caused by the distribution of benefits between village B and village N, government subsidies, property rights protection, village rules and regulations are required. Besides, the leading role of rural grassroots organizations should be given full play, and villagers’ self-governing system needs to be improved.